Evaluation of purine utilization by Lactobacillus gasseri strains with potential to decrease the absorption of food-derived purines in the human intestine. (1st December 2016) - Yamada, N.; Iwamoto, C.; Kano, H.; Yamaoka, N.; Fukuuchi, T.; Kaneko, K.; Asami, Y.
Abstract: It is well accepted that frequent and heavy intake of purine-rich foods causes elevation of serum uric acid levels, which is a risk factor of hyperuricemia. Reducing intestinal absorption of dietary purines may attenuate the elevation of serum uric acid levels and exacerbation of hyperuricemia. This reduction may be achieved by the ingestion of lactic acid bacteria that take up purines in the intestine. In this study, we investigated the degree of uptake and utilization of purines of three lactobacilli strains. Among them, Lactobacillus gasseri PA-3 (PA-3) showed the greatest incorporation of 14 C-adenine. PA-3 also incorporated 14 C-adenosine and 14 C-AMP. Additionally, using defined growth medium, PA-3 demonstrated greater proliferation in the presence of these purines than in their absence. Although further investigation is required, ingestion of PA-3 may lower serum uric acid levels by reducing intestinal absorption of purines in humans.